Infections in patients with solid tumors of the central nervous system and head and neck (Actualizaciones en Sida e Infectología, 2018)
Solid tumours represent 90 percent of the oncohematologic pathologies diagnosed in Argentina. Infections are one of the most frequent complications causing important morbidity and mortality and delay in prosecution of their specific treatment. The type of infection depends on the specific site of the tumour, the presence of post obstructive phenomena, the treatment administered, comorbidity and local epidemiology, among others. New therapies are being continuously incorporated to the armamentarium of cancer treatment such as new chemotherapies regimes, target therapy and immunotherapy. The management of adverse events and infectious complications associated with them are a challenge for the physician in charge of these patients.The epidemiology, prevention and management of the most frequent infectious complications in patients with tumours of the central nervous system and head and neck are reviewed in this paper.
Keywords: Solid tumours; head and neck; central nervous system; infection; surgery; radiotherapy; chemotherapy; target therapy; immunotherapy